Improved testing characterization on radio frequency connector in calibration system - Tan, Ming Hui (2021)
For extending the dynamic range of measuring equipment, radio frequency connectors are found in a wide variety of electronic types of equipment. An important part of characterizing RF microwave circuits and devices required precision in S-parameters measurement. Variety type of dimension and frequency range can be found with RF connector. The main issue is the RF connector neglects the insertion loss causing an unknown error contributed to an RF system in calibration. The unknown insertion loss could create a phenomenon that triggered a false failure in the RF system. The objective of this study is to develop and calculate the Error normalize ratio for characterizing RF connectors, identify the unique RF connector characterization process and techniques associate with measurement uncertainty calculation by using the vector network analyzer, and integrate the power sensor calibration system with RF connector mismatch into the component of the calculation. This is to determine the methodology into several effective techniques of RF connector insertion loss, port match, measurement uncertainty, decision rule to a newly developed product specification in an RF manufacturing process into a power sensor calibration system as the final product to the end customer. In addition, the method applied in this study refers to the international requirements example ANSI/NCSL Z540.3 released in the year 2006, ISO/IEC 17025:2017 released in the year 2017, and ISO GUM (JCGM 100:2008) released in the year 2008 to meet the quality results. The expected outcome of this study would provide a summary of RF connector mismatch is extremely important to an RF measurement system that required extensive research by applying appropriate equipment in precision measurement.